Frequent fires do not affect sexual expression and reproduction in Vachellia caven. (6th March 2019) - Marquez, Victoria; Carbone, Lucas M.; Aguilar, Ramiro; Ashworth, Lorena
Abstract: In environments with high fire frequency the impoverishment of abiotic resources may favour male sexual expression in plants as it is less costly than female expression. Also, fire can modify pollinator communities and thus affect plant reproduction. Here we evaluate the effect of frequent fires on sexual expression, pollination and reproductive success of Vachellia caven (Leguminosae), an andromonoecious tree that is highly dependent on animal pollination and is abundant in burned sites. We expect that increased fire frequency will favour maleness but it will decrease reproductive success due to abiotic resource depletion in repeated burned sites. To test this, we selected focal plants in three unburned sites and three frequently burned sites and measured their sexual expression, basal diameter, pollination and fruit set. The proportion of male inflorescences per plant was not affected by fire and it was negatively related with the diameter of the plant. The proportion of pollinated flowers was not affected by fire, and fruit set increased with maleness only in frequently burned sites. These results indicate that V. caven is adapted to regimes of high fire frequency: not only was there similar fruit set in both burned and unburned sites, but more male plants had higher fruit set in burned sites. Despite the soil impoverishment triggered by repeated fires, V. caven is able to maintain its sexual and reproductive functions, allowing it to persist and maintain viable populations in fire‐prone environments. Abstract in Spanish is available with online material.